Probiotic Properties of Bacillus pumilus, Bacillus sphaericus and Bacillus subtilis in Black Tiger Shrimp (Penaeus monodon Fabricius) Culture - Watchariya Purivirojkul; Monchan Maketon; Nontawith Areechon (Agriculture and Natural Resources, 2005)
Three species of the genus Bacillus namely B. pumilus,B. sphaericus, and B. subtilis were isolated from the intestine of Penaeus monodon and tested for possible potential as a probiotic in black tiger shrimp rearing. The competition, colonization and inhibition activities of Bacillus spp. on Vibrio harveyi, a known pathogen in black tiger shrimp aquaculture were conducted. Transmission electron microscope observations showed the size of V. harveyi’s cell colonized by B. pumilus, B. sphaericus and B. subtilis to be smaller compare with its normal cell. This morphological deviation was permanently changed in every generation of V. harveyi. In addition, three species of the Bacillus could be grown in a wild range of conditions, these include salinity between 0-8 % NaCl, pH from 4 to 11 and temperature ranging of 25-50 oC except B. sphaericus which was not amenable to grow at 50 oC. Therefore, B. pumilus, B. sphaericus and B. subtilis showed promising potential to be used as a probiotic in black tiger shrimp. As for probiotic properties in black tiger shrimp, the results shown that number of bacteria in intestinal tracts of the shrimps were increased in all treatments from 216 to 803% of the control group, and the amount of V. harveyi, were found reduced from 87.53 to 99.76% of the control, as also confirmed by scanning electron microscope observations. B. subtilis, the mixture of B. sphaericus+ B. subtilis, and B. pumilus+ B. sphaericus+ B. subtilis in culture media showed immunostimulatory features measured by total hemocytes, phenol oxidase, superoxide anion, clearance ability and bactericidal activity which increased by 20.02-23.10, 26.02-39.43, 53.45-66.04, 44.68-59.57 and 50.00%, respectively.